Coexistent anti-GFAP and anti-MOG antibodies presenting with isolated meningitis and papillitis: more support for overlapping pathophysiology. Issue 1 (24th March 2022) - Martin, Andrew J; Strathdee, James; Wolfe, Nigel
Abstract : Background: Anti-myelin oligodendrocyte glycoprotein (MOG)-associated disorders are heterogeneous and associated predominantly with central nervous system demyelination. Anti-glial fibrillar acidic protein (GFAP) conditions are much rarer and involve meningoencephalomyelitis with papillitis in addition to characteristic imaging findings and are generally a severe condition. Multiple autoantibodies can exist in patients and may support overlapping pathophysiological mechanisms. The co-occurrence of MOG and GFAP antibodies, however, is rare, with only two cases previously reported. Case: A 53-year-old man presented with headache and fevers, with quick resolution, though with the later development of asymptomatic papillitis. He had a full recovery without the need for immunotherapy. He underwent extensive investigations and was found to have both anti-GFAP and anti-MOG antibodies in the cerebrospinal fluid. Extensive other immunological and infectious investigations were negative. Imaging was largely unremarkable. Conclusions: This is the third case of overlapping anti-GFAP and anti-MOG antibody-associated syndrome of self-limited lymphocytic meningitis, serving to expand the phenotype. Clinicians should consider testing for GFAP and MOG antibodies in otherwise unexplained meningitis, particularly with associated papillitis. This case may also help provide future insights into the pathophysiology of each condition.